Penurunan Residu Pestisida Tebukonazol dan Trifloksistrobin pada Umbi Bawang Merah dengan Budidaya Organik Berbasis Biopestisida di Desa Bulugunung Kecamatan Plaosan Kabupaten Magetan - Lia Iswindari Mukaromah; Sri Wiyatiningsih; Tri Mujoko (BPFP Universitas Bengkulu, 2022)
[REDUCTION OF PESTICIDE RESIDUES Tebukunazol AND Trifloksistrobin ON ORGANIC BULB SHALLOT CROPS WITH BIOPESTICIDE BASED IN BULUGUNUNG VILLAGE, PLAOSAN, MAGETAN REGENCY]. Shallot plants are agricultural commodities that have a high and economic value. The continuous use of pesticides to increase Shallot production will harm the environment. The active pesticides of Tebukonazol and Triflooxystrobin are one of the fungicides to overcome moler disease. Maximum Residue Limit (BMR) on shallot bulbs for active substance Tebukonazol of 0.1 mg/kg while for active substances Trifloksistrobin of 0.01 mg/kg. To reduce the pesticide residues, efforts are needed through the application of biopesticides. This research was conducted in March-May 2021 in Bulugunung Village of Plaosan District of Magetan Regency. Analysis of pesticide residues Tebukonazol and Trifloksistrobin was carried out at the Laboratory of The Industrial Research and Consulting Center (BPKI) Surabaya. The research was one factor, conducted in a Complete Randomized Design (CRD) consisting of 4 treatments with 6 replications, namely: Treatment (A): Conventional cultivation, Treatment (B): Fobio (seeds and plants), Phonska Fertilizer, P-Phosfat, SP-36, KCl, and ZA, Treatment (C): Manure to the soil and Soil sterilization with Fobio, as well as pesticide application, Treatment (D): Giving soil manure and soil sterilization with Fobio, and the application of Fobio (seeds and plants). Data analysis was conducted in analysis of variance (ANOVA), followed by the the Honesty Significant Difference (HSD) at a level of 5% if the F test shows a significant effect. The results showed that the treatments (B) and (D) of Fobio applications in seeds and plants have the lowest pesticide residue values of Tebukonazol and Trifloksystrobin compared to treatments (A) and (C) that use chemical pesticides.